2016
DOI: 10.1111/jfpp.12951
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Virgin Olive Oil Supplemented withZataria multifloraBoiss. andRosmarinus officinalisL. Essential Oils During Accelerated Storage

Abstract: The aim of this study was to investigate the effects of Zataria multiflora Boiss. and Rosmarinus officinalis L. essential oils (EOs) on oxidative stability of virgin olive oil (VOO). Antioxidant activity indices (peroxide, p-anisidine, K 232 and K 268 values) of EOs were compared with those of BHT and b-carotene. As a result, the lowest peroxide value, p-anisidine value, K 232 and K 268 values were determined in samples containing BHT and Z. multiflora EO. The R. officinalis EO significantly reduced VOO oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…Recently, the essential oil of T. polium was demonstrated to control the elevation of TPC of canola oil during the storage [30]. Z. multifiora and Rosmarinus officinalis essential oils were demonstrated to hinder TBARS, K 232 , and K 268 of olive oil during the storage [32]. The results were in line with these reports.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Recently, the essential oil of T. polium was demonstrated to control the elevation of TPC of canola oil during the storage [30]. Z. multifiora and Rosmarinus officinalis essential oils were demonstrated to hinder TBARS, K 232 , and K 268 of olive oil during the storage [32]. The results were in line with these reports.…”
supporting
confidence: 80%
“…The amount of MDA and polar compounds is determined as TBARS and TPC, respectively. In addition, conjugated dienes and conjugated trienes could be generated in the oxidation of edible oils, which in turn induce absorption peaks at 232 nm and 268 nm so that K 232 and K 268 nm could be applied to assess the levels of conjugated dienes and conjugated trienes [6,7,32]. During the high-temperature storage process, the values for TBARS, TPC, K 232 , and K 268 sharply rose in sample VI (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results were also in agreement with that of AV, PV, IV, AnV, TBARS, FFA, TPC and TOC, verifying the antioxidant effect of the essential oil in the storage of sunflower oil. Consequently, CEO was able to be used as natural antioxidant during the storage of sunflower oil to substitute the synthetic antioxidant, TBHQ (Keramat, et al, 2017).…”
Section: Stability Evaluation Of Ceo On Sunflower Oil During Acceleramentioning
confidence: 99%
“…β-Carotene had the highest conjugated diene compounds. Keramat et al [30] evaluated oxidative stability of virgin olive oil supplemented with Zataria multiflora and Rosmarinus officinalis essential oils in comparison with those of BHT and β-carotene. They reported that virgin olive oil supplemented with BHT and essential oils had significantly lower K 232 than control at the end of storage period, while K 232 of virgin olive oil containing β-carotene was higher than that of control at the same time.…”
Section: Sbomentioning
confidence: 99%